INTERVENING FACTORS IN THE LENGTH OF HOSPITAL STAY OF PATIENTS WITH COVID-19 - Silva, Geicilane de Sousa Silva (2023)
Objective: To analyze the factors intervening in the length of hospital stay of patients with COVID-19 admitted to an intensive care unit. Method: A cross-sectional, quantitative study was conducted with 119 patients admitted to a COVID-19 Intensive Care Unit of a public hospital in northeastern Brazil. Sociodemographic and clinical data were collected and their association with length of hospital stay was tested by Pearson's chi-square (p<0.05). The strength of this association was tested by the odds ratio, and logistic regression (backward method) was used for model fitting. Results: The majority (92.4%) of participants were considered to be in the risk group for the disease, with Systemic Arterial Hypertension (38.7%) and Diabetes Mellitus (36.1%) being the most prevalent comorbidities. Of the 119 patients admitted, 75 (63%) stayed for up to 10 days. In the final regression model, male patients (p<0.001), using chloroquine (p=0.013) and intubated (at admission) remained hospitalized for longer than 10 days. Conclusions: The study showed that the length of hospital stay was influenced by the variables gender, type of treatment used and oxygen therapy support. Some patients, who already presented previous comorbidities, evolved to severe cases of the disease. However, others were able to progress to cure. Knowing these factors allows the improvement and adequacy of care practices provided to these patients, especially in strategies that can improve the quality of service and reduce the length of hospital stay.